The Effect of Group Guidance With Cognitive Therapy Techniques To Lower Social Phobia Anxiety - Latifah Ritonga; Alfin Siregar (Dinasti Publisher, 2024)
Social phobia is an illogical concern for the negative view of the individual. People with social phobia consider that the individual who sees them judges him, therefore the individual tends to avoid social situations. Cognitive therapy techniques in group guidance are techniques contained in group guidance that aim to enable students to speak in front of many people; Students are also able to provide opinions, ideas, suggestions, responses, and feelings to the public.This study aims to determine the effectiveness of cognitive therapy techniques through group guidance services for social megataphobia in adolescents. This study uses a quantitative method with a pre-experiment design with a one-group pretest posttest design. The population of this study is class VII at Madrasah Tsanawiyah Private Islamiyah Hessa Air Genting as many as 56 people. The research sample was 8 people who had a high category of social phobia. Samples were taken using the purposive sampling technique. Data was collected through a questionnaire using a Likert scale. Data analysis used the Wilcoxon Signed Ranks Test with an asymp significance value, Sig (2-tailed) of 0.012 (?) from the predetermined significance level of 0.05. This means that cognitive therapy techniques through group guidance services are effective in preventing social phobia in adolescents.